Students’ interest level in English online learning - Linda Puspita; Thalia Savira Ristianti; Soviyah Soviyah (Teaching English as a Foreign Language Journal, 2022)
English is one of the subjects that students in Indonesia are required to study, including during the COVID-19 pandemic situation. As a result of the the pandemic, the English learning process is conducted online. Therefore, students are expected to adapt to this new learning mode, and to be interested in it as well. This research aims to find out the level of the students’ interest in learning English online. The research utilizes descriptive quantitative method. A questionnaire is used as the research instrument. Taking SMPN 2 Girimulyo junior high school, Yogyakarta, Indonesia as the research setting, it involves 40 students which consist of 25 female students and 15 male students. The research data are collected online through Google form distributed to the respondents to reveal their interest in learning English online. The study findings show that 77% of students are interested in learning English online, 66% of the students master the material, and the interaction between students and teacher is very good reaching perfect score of 100%. However, when asked about their preference, 60% of the students prefer learning English offline under face-to-face mode.